2020
DOI: 10.1038/s42003-020-0873-9
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer molecular analysis of the RB tumor suppressor pathway

Abstract: The retinoblastoma tumor suppressor gene (RB1) plays a critical role in coordinating multiple pathways that impact cancer initiation, disease progression, and therapeutic responses. Here we probed molecular features associated with the RB-pathway across 31 tumor-types. While the RB-pathway has been purported to exhibit multiple mutually exclusive genetic events, only RB1 alteration is mutually exclusive with deregulation of CDK4/6 activity. An ER+ breast cancer model with targeted RB1 deletion was used to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 49 publications
4
55
0
Order By: Relevance
“…Accordingly, in various tumors (retinoblastoma, bladder, breast, colorectal and small cell lung carcinoma (SCLC) tumors), γtubulin and RB1 moderate each other's expression, and in the absence of γtubulin and RB1, the uncontrolled transcriptional activity of E2Fs upregulates apoptotic genes, causing cell death [88,108]. The RB pathway is one of the most well-described tumor suppressor pathways, and it is found to be highly mutated in a large spectrum of cancers [144,145]. Using the cbioportal [143], we found that among 31 subtypes of cancer, 30% exhibit defects in the RB pathway, with 7% of the patients exhibiting a loss of RB1 [144].…”
Section: Gamma-tubulin In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, in various tumors (retinoblastoma, bladder, breast, colorectal and small cell lung carcinoma (SCLC) tumors), γtubulin and RB1 moderate each other's expression, and in the absence of γtubulin and RB1, the uncontrolled transcriptional activity of E2Fs upregulates apoptotic genes, causing cell death [88,108]. The RB pathway is one of the most well-described tumor suppressor pathways, and it is found to be highly mutated in a large spectrum of cancers [144,145]. Using the cbioportal [143], we found that among 31 subtypes of cancer, 30% exhibit defects in the RB pathway, with 7% of the patients exhibiting a loss of RB1 [144].…”
Section: Gamma-tubulin In Cancermentioning
confidence: 99%
“…The RB pathway is one of the most well-described tumor suppressor pathways, and it is found to be highly mutated in a large spectrum of cancers [144,145]. Using the cbioportal [143], we found that among 31 subtypes of cancer, 30% exhibit defects in the RB pathway, with 7% of the patients exhibiting a loss of RB1 [144]. In brain tumors, high expression of γtubulin is associated with high-grade astrocytomas and glioblastomas, as compared to low-grade astrocytomas, which exhibited weaker γtubulin staining [146].…”
Section: Gamma-tubulin In Cancermentioning
confidence: 99%
“…Using MSigDB oncogenic signatures, we found that MEC transcriptomes were enriched with the oncogenic signatures (Supplemental Table 2), such as cAMP-induced signature (cAMP-up), oncogenic EGFR-induced signature (EGFR-up), and RB1/RBL1 loss-induced signature (RB.107_DN-up) (Figure 4F). Moreover, a CDK4/6-RB integrated signature, identified from a recent pan-cancer molecular analysis (41), was also found to be overrepresented in fusion-induced MEC (Figure 4G). These data were again in agreement with the CREB activation and enhanced EGFR signaling in human MEC, as we previously reported (32).…”
Section: Resultsmentioning
confidence: 77%
“…Accordingly, in various tumours (retinoblastoma, bladder, breast, colorectal and small cell lung carcinoma (SCLC) tumors), tubulin and RB1 moderate each other's expression, and in the absence of tubulin and RB1, the uncontrolled transcriptional activity of E2Fs upregulates apoptotic genes, causing cell death [98,103]. The RB pathway is one of the most well described tumour suppressor pathways, and it is found to be highly mutated in a large spectrum of cancers [143,144]. Using the cbioportal [142], we found that among 31 subtypes of cancer, 30% exhibit defects in the RB pathway, with 7% of the patients exhibiting a loss of RB1 [143].…”
Section:  Tubulin In Cancermentioning
confidence: 99%
“…The RB pathway is one of the most well described tumour suppressor pathways, and it is found to be highly mutated in a large spectrum of cancers [143,144]. Using the cbioportal [142], we found that among 31 subtypes of cancer, 30% exhibit defects in the RB pathway, with 7% of the patients exhibiting a loss of RB1 [143]. In brain tumours, high expression of tubulin is associated with high grade astrocytomas and glioblastomas, as compared to low grade astrocytomas, which exhibited weaker tubulin staining [145].…”
Section:  Tubulin In Cancermentioning
confidence: 99%